2022
DOI: 10.3390/ijerph19042221
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Minutes Identified as the Threshold for Development of Pain in Low Back and Feet Regions, and Predictors of Intensity of Pain during 1-h Laboratory-Based Standing in Office Workers

Abstract: This study with 40 office workers investigated (a) the effect of time spent standing on low- back and lower limb pain during a 1-h laboratory-based task; (b) the standing time after which a significant increase in pain is likely; and (c) the individual, physical and psychosocial factors that predict pain. The primary outcome was bodily location of pain and pain intensity on a 100-mm Visual Analogue Scale recorded at baseline and every 15 min. Physical measures included trunk and hip motor control and endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This study determined 30 minutes of standing as a threshold for the development of pain in the lower back region. [18] A study conducted on newsreel cameramen revealed that carrying a mobile camera on their shoulder may cause suprascapular nerve entrapment and shoulder pain, which can be considered an occupational disorder. [19] In our study, 56.98% of the participating cameramen reported shoulder pain, which may have been influenced by suprascapular nerve entrapment due to the contact stress and pressure generated by handling a portable shoulder camera.…”
Section: Discussionmentioning
confidence: 99%
“…This study determined 30 minutes of standing as a threshold for the development of pain in the lower back region. [18] A study conducted on newsreel cameramen revealed that carrying a mobile camera on their shoulder may cause suprascapular nerve entrapment and shoulder pain, which can be considered an occupational disorder. [19] In our study, 56.98% of the participating cameramen reported shoulder pain, which may have been influenced by suprascapular nerve entrapment due to the contact stress and pressure generated by handling a portable shoulder camera.…”
Section: Discussionmentioning
confidence: 99%